Tinjauan Yuridis Konten Youtube sebagai Objek Jaminan di Bank - Rebica Stevani Soinbala; Ufran Ufran (Indonesia Berdaya, 2023)
Youtube is also increasingly in demand because it can become a new niche for finding or increasing income (salary). With this rapid development, more and more people are creating YouTube accounts to use as a business as a source of income. YouTube itself opens wide opportunities for content creators who want to create content to earn income. Currently in Indonesia there are many popular names among YouTubers. With the development of the content creator profession in the digital media industry, they earn a higher income than people in general. So that digital media gets a trial opportunity to ensure that the content created is worthy of being used as a loan value at the bank. This research is normative-juridical research. By using a statutory approach and a conceptual approach. Data collection techniques were carried out using the library study method. The data analysis technique was carried out in a qualitative descriptive manner. Article 16 of the 2014 Copyright Law has regulated a new provision regarding legal certainty to guarantee copyrights (copyright works) as the basis for borrowing money. issued Government Regulation (PP) No. 24 of 2022 concerning Regulations for Implementing Law No. 24 of 2019 concerning the Creative Economy which regulates intellectual property-based financing schemes. In the procedure for binding YouTube account content as a fiduciary guarantee object that is categorized as copyright, it must first be registered and ratified at the Director General of Intellectual Property at the Ministry of Law and Human Rights.